Effects Of Low Calories, High Fibre Diet On Weight And Body Condition Score In Overweight Or Obese Prone Small Breed Dogs In Malaysia - DR. AMIRUL FAIZ MOHD AZMI (2024)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement of the course DVT 55204 - Research Project.Canine obesity is a growing concern due to its association with metabolic and chronic diseases.This study evaluated the effects of a low-calorie, high-fibre diet on weight loss, body condition score (BCS), satiety, and overall health in overweight small-breed dogs. The intervention also examined owner compliance and the safety of the feeding regimen, targeting a weekly weight loss rate of 0.5–1.0% body weight. Six small-breed overweight or obese dogs, averaging seven years old, were divided into a trial group and a control group, each with three dogs. Initial mean body weights were 9.33 kg and 8.00 kg, while mean BCS averaged 8 and 6.67 for the trial and control groups, respectively. The trial group was fed a low-calorie, high-fibre diet, while the control group received a standard commercial diet for four weeks. A slight mean weight reduction was observed in the trial group (-0.17 kg) (p>0.05), while the control group showed a minor weight gain (+0.63 kg) (p>0.12). Mean BCS in the trial group decreased from 8.00 to 7.33 (p>0.05), and the control group exhibited a significant reduction from 6.67 to 5.67 (p<0.001). Satiety and palatability were satisfactory in the trial group, with minimal food leftovers.These results indicate the diet is metabolically safe but may require an extended period or additional interventions for significant weight loss. Further studies are needed to refine canine weight management protocols. Keywords: Body condition score, Canine obesity, High-fibre diet, Low-calorie, Weight loss.